The Implementation of Lean Manufacturing System in Production Process Theoretical Analysis and Empirical Investigations. An Empirical Study on the Manufacturing Companies in Poland - Al-Nusyrat, Mudar (Archives of Business Research, 2023)
Purpose: The purpose of this paper is to investigate the implementation of Lean Manufacturing System (LMS) in the manufacturing companies of Poland. Design/methodology/approach: Using a survey questionnaire, data was collected against the most common lean practices and tools which formed the Lean House (LH) presented by Liker (2004), from 40 manufacturing companies acting in Poland. Lean practices and tools were clustered into five groups according to its position in the LH structure: The roof: the goal of lean manufacturing system, the lift pillar: Just-in-Time principle (JIT), the right pillar: Jidoka tool, the center: People who identify wastes and solve problems to insure continuous improvement, and the foundation: Lean Tools: 5S, Standardization, Visual Management and Production levelling. The responding companies were categorized according to their respective field of production and the company size (big, middle and small). 181 manufacturing companies acting in the manufacturing field of Poland were contacted, 40 companies participated and 3 of them were excluded due to lack of implementation. The results identified by statistical analysis to find out the Average and the Percentage of implementing each and all Lean Manufacturing practices and tools. Findings: The manufacturing companies in Poland have implemented various lean practices and tools to a certain extent. However, the results suggest that the adoption of lean manufacturing as a fully integrated, systematic, and cultural approach may not be highly developed enough. Hence, reaping the maximum benefits of the LMS in those companies may be doubted. Research limitations/implications: Since the sample size is not very large, the results need to be considered with caution as being limited to the participated companies. Practical implications: The paper gives an indication about the status of the implementation of LMS in the Polish manufacturing companies. It also includes a description for better understanding of Lean concept and practices through a specific literature review. Originality/value: The implementation of LMS was researched widely in different countries all over the world and some of them are EU countries. Despite that, there is a lack of similar studies in the manufacturing companies in the 10 countries which have joined the EU in the year 2014, and specifically in Poland. Moreover, this paper also illustrates a better understanding of the Lean concept through a literature review of selected recognized articles dealt with this concept.